Association effect of in-office and nightguard vital bleaching on dental enamel microhardness - J.A. Rodrigues; Maria Carolina Guilherme Erhardt; Giselle Maria Marchi; L.A.F. Pimenta; Gláucia Maria Bovi Ambrosano (Universidade Estadual de Campinas, 2015)
The aim of this study was to evaluate "in vitro" the microhardness of dental enamel subjected to in-office and nightguard vital bleaching agents: 37% carbamide peroxide-CP37 (Whiteness Super-FGM) and 10% carbamide peroxide-CP10 (Whiteness Perfect-FGM). Enamel fragments measuring 3 x 3mm (n=18) were embedded in polystyrene resin and polished. They were treated 1h once a week with the CP37 and 8h every day with CP10 for 21 days. The remainder of the time they were stored in remineralization solution. Microhardness measurements were completed with a Knoop diamond in a microhardness tester with 50g static load prior to the exposure to bleaching agents and 7, 14, 21, 28, and 35 days after that Split Plot ANOVA followed by Tukey's test were performed. The test showed no significant differences in the enamel microhardness before, during, or after bleaching treatment. Conclusions: It can be concluded that the combination of in-office and nightguard vital bleaching agents do not alter the enamel microhardness "in vitro"